Şıpat - Ahmet Cevat, Baytar Yüzbaşı Doktor. (İstanbul İstanbul İstanbul İstanbul İstanbul)
7 kitap 1 ciltte (1. kitap 43, [1[ s., 2. kitap 33 s., 3. kitap 96 s., 4. kitap 128, [1] s., 5. kitap 108, [2] s., 6. kitap 53 s., 7. kitap 46 s.)